2016
DOI: 10.13109/zptm.2016.62.3.270
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Modifiable Determinants of Non-Adherence in Adult Kidney Transplant Recipients in a German Sample

Abstract: Zusammenfassung Prävalenz und modifizierbare Determinanten der Non-Adhärenz bei erwachsenen Nierentransplantatempfängern in einer deutschen StichprobeFragestellung: Das Ziel dieser Querschnittstudie war die Untersuchung der Prävalenz und der modifizierbaren Determinanten der Non-Adhärenz bei erwachsenen Nierentransplantatempfängern in der Nachsorge. SummaryObjectives: The aim of this cross-sectional study was to investigate the prevalence and the modifiable determinants of non-adherence in adult kidney trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
2
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 33 publications
(36 reference statements)
1
15
2
3
Order By: Relevance
“…In a meta-analysis, the chances of graft failure were seven times higher in non-adherent patients compared to adherent patients (23) and a study that used BAASIS® to evaluate 74 patients found 14.3% nonadherence. (10) However, the general score for nonadherence found would be higher than cited, with a score similar to results of a Brazilian randomized study that used an education intervention and found adherence of 46.4% in the control group and 14.5% in the intervention group (p=0.001). (18) A prospective cohort study with 1,505 patients in which 924 (61.4%) underwent KTP showed that non-adherence increased continually from six months until three years of follow-up; this finding supports the early adoption of measures supporting adherence to immunosuppressive therapy.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…In a meta-analysis, the chances of graft failure were seven times higher in non-adherent patients compared to adherent patients (23) and a study that used BAASIS® to evaluate 74 patients found 14.3% nonadherence. (10) However, the general score for nonadherence found would be higher than cited, with a score similar to results of a Brazilian randomized study that used an education intervention and found adherence of 46.4% in the control group and 14.5% in the intervention group (p=0.001). (18) A prospective cohort study with 1,505 patients in which 924 (61.4%) underwent KTP showed that non-adherence increased continually from six months until three years of follow-up; this finding supports the early adoption of measures supporting adherence to immunosuppressive therapy.…”
Section: Discussionsupporting
confidence: 76%
“…Sociodemographic variables showed a higher score for adherence among married recipients (94.8%) than among single (80.4%) or divorced (64.3%) recipients and autonomous professionals (76.9%). Although the influence of the existence of a conjugal partner is not conclusive in some publications, a recent study (10) showed that being separated or divorced was a factor associated with nonadherence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This global improvement in graft failure and survival rates is most likely due to several factors, including either technological and surgical technique advancements or improvement in medical management and immunosuppressive therapy -it may not be necessarily due to improved medication adherence. (28)(29)(30)(31)(32)(33) Treatment for management of grafts consists of a combination of immunosuppressive agents with different mechanisms of action. This strategy minimizes morbidity and mortality individually associated to each immunosuppressive agent class, maximizing global treatment efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Verglichen mit anderen Transplantationspatienten ist die Medikamenten-Non-Adhärenz bei Nierenempfängern am häufigs-ten, gefolgt von Herz-und Lebertransplantierten (Dew et al 2007). Aktuelle Studien fanden bei nierentransplantierten Patienten in verschiedenen deutschen Transplantationszentren selbstberichtete Non-Adhärenz-Raten von 24 % (Reber et al 2016) bis 37 % (Pabst et al 2015). Denhaerynck et al (2009) kommen bei einem systematischen Überblick zu dem Ergebnis, dass die selbsteingeschätzte Non-Adhärenz der Nierentransplantationspatienten bei 28 % liegt und 20 % der späten akuten Abstoßungsreaktionen sowie 16 % der Transplantatverluste auf dieses problematische Gesundheitsverhalten zurückzuführen sind.…”
Section: Einleitung Und Theoretischer Hintergrund Des Behandlungsmanualsunclassified